2016
DOI: 10.1007/jhep03(2016)080
|View full text |Cite
|
Sign up to set email alerts
|

The light bound states of supersymmetric SU(2) Yang-Mills theory

Abstract: Supersymmetry provides a well-established theoretical framework for extensions of the standard model of particle physics and the general understanding of quantum field theories. We summarise here our investigations of N = 1 supersymmetric Yang-Mills theory with SU(2) gauge symmetry using the non-perturbative first-principles method of numerical lattice simulations. The strong interactions of gluons and their superpartners, the gluinos, lead to confinement, and a spectrum of bound states including glueballs, me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 50 publications
4
57
1
Order By: Relevance
“…For β = 1.5 this gives k = 0.675(24). The corresponding number for β = 1.7, ensembles M, O, P, is k = 0.751 (8). For comparison, we get k = 0.817(36) from N, O, P, Q, and k = 0.817(24) from L -P. Figure 6 shows the averaged logarithmic masses for β = 1.7 and the fit with k = 0.751.…”
Section: Jhep01(2018)119mentioning
confidence: 97%
See 1 more Smart Citation
“…For β = 1.5 this gives k = 0.675(24). The corresponding number for β = 1.7, ensembles M, O, P, is k = 0.751 (8). For comparison, we get k = 0.817(36) from N, O, P, Q, and k = 0.817(24) from L -P. Figure 6 shows the averaged logarithmic masses for β = 1.7 and the fit with k = 0.751.…”
Section: Jhep01(2018)119mentioning
confidence: 97%
“…A study of SU (2) with N f = 1 fermion flavours [7] gives indications for IRconformal behaviour, too. The case of N f = 1/2 describes one flavour of Majorana fermions and corresponds to N = 1 supersymmetric Yang-Mills theory, which has been studied by our collaboration, see [8] and references therein. This theory is QCD-like concerning its scaling behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated the particle spectrum of the theory and observed the expected degeneracy of the states in the lightest supermultiplet [6]. We have now extended our studies to the multiplet of excited states, and first results have been reported in a contribution to the Lattice2017 conference [7].…”
Section: Jhep03(2018)113mentioning
confidence: 99%
“…Alternative tunings of the coefficient are possible. In the SU(2) case we have tested a tadpole resummation [6], that leads to a considerable improvement of the mass degeneracy for finite lattice spacings. At our current parameter range the value of c sw obtained with the proposed tadpole formula is not much different from the one-loop prediction.…”
Section: Jhep03(2018)113mentioning
confidence: 99%
See 1 more Smart Citation